First Aid Training on Near Drowning and Emergency System Activation to Employees of Hotel Quest San Denpasar - Tanjung Subrata; Komang Trisna Sumadewi; Aulia Iefan Datya (UNUSA Press, 2023)
It is possible to use the global decline in the Covid-19 epidemic as a trigger for the revival of Bali's tourism sector. Bali tourism includes a significant portion of water sports like surfing, diving, rafting, and swimming on beaches, lakes, and rivers. Swimming pools and other activities are available at amusement parks. One of the most common events in water tourism is almost drowning. There were 9 fatalities and 300 drowning instances in the Kuta beach area alone, according to the 2018 data. Because it is essential for tourist actors, especially those associated with water leisure, to acquire Basic Life Support (BLS) training, especially in saving drowning victims, the success of the rescue of drowning victims greatly depends on the speed and precision of administering BLS. The administration of the Quest San Denpasar Hotel, where Partners work, wishes to offer first aid training for accidents, particularly for drowning victims, as none of the hotel staff have ever had first aid training. Ten hotel staff members attended the training on October 29, 2022, at the Quest San Denpasar Hotel. The training provided is in the form of theory and practice of identifying drowning victims, activating the emergency system, evacuating victims from the waters to land, providing BLS, and sending victims to the nearest health facility. Before the training, a pre-test was carried out and afterward, a post-test was carried out, from the results of these tests it could be concluded that there was an increase in the participants' knowledge of 32%, and from BLS practice all participants were able to assist properly.